1997
DOI: 10.1021/la970388k
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly in Mixtures of Sodium Alkyl Sulfates and Alkyltrimethylammonium Bromides:  Aggregation Behavior and Catalytic Properties

Abstract: Two aqueous mixtures of cationic and anionic surfactants have been studied by means of conductometry, transmission electron microscopy, and microcalorimetry. Their catalytic effects on the decarboxylation of the kinetic probe 6-nitrobenzisoxazole-3-carboxylate (6-NBIC) were also examined in some detail. The mixtures differ profoundly in the hydrophobic match between both surfactant tails, which is perfect for dodecyltrimethylammonium bromide (DTAB) and sodium dodecyl sulfate (SDS) and poor for hexadecyltrimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 53 publications
2
57
0
Order By: Relevance
“…comparable to those observed for accelerated vesicle formation (31,49) and other lipid catalysis reactions (50)(51)(52). For computer simulations of the dynamics of such molecular assemblies, we use chemical kinetics rules based on the previously proposed Graded Autocatalysis Replication Domain (GARD) model (38,39).…”
Section: Resultssupporting
confidence: 84%
“…comparable to those observed for accelerated vesicle formation (31,49) and other lipid catalysis reactions (50)(51)(52). For computer simulations of the dynamics of such molecular assemblies, we use chemical kinetics rules based on the previously proposed Graded Autocatalysis Replication Domain (GARD) model (38,39).…”
Section: Resultssupporting
confidence: 84%
“…These compounds induce rate constants of an order of magnitude of 10 -3 s -1 [34][35][36]. In addition, the k obs found for cationic micelles formed from nhexadecyltrimethylammonium bromide (CTAB) at 30°C is in the order of magnitude of 10 -4 s -1 [25,37], which is comparable with the k obs found for DHAB at 35°C. Comparable k obs values at a temperature of 30° C are also found for vesicles containing different amounts of di-noctadecyldimethylammonium chloride (DODAC) [28].…”
Section: Resultsmentioning
confidence: 51%
“…Here we report the kinetic effects of two types of DHAB/C n OH (n= 10, 16) mixtures on the unimolecular decarboxylation of 6-nitrobenzisoxazole-3-carboxylate (6-NBIC) (Scheme 1). This kinetic probe has been widely used in biophysical studies and is sensitive to the local micropolarity [23][24][25][26], which makes it a proper model reaction for investigation of composition changes in membranes. In addition, the reaction is also highly sensitive to hydrogen-bonding interactions which stabilize 6-NBIC by forming hydrogen-bonds with the carboxylate group [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…6 It has been shown that such vesicles can accelerate the 6-NBIC reaction by approximately 30% compared to cationic micelles. 7 Synthetic cationic vesicles are also 4-15times more efficient for the decarboxylation than phospholipid vesicles. 8 The interaction between the cationic head group and the 6-NBIC anion promotes binding at the vesicular interface, thereby decreasing the number of hydrogen bonding opportunities between water and the substrate, with a concomitant increase of the rate constant.…”
Section: Introductionmentioning
confidence: 99%